Book profile: September 11: religious perspectives on the causes and consequences - DaPonte, Paul J (The journal for cultural and religious theory, 2007)
A profile of Ian Markham and Ibrahim M. Abu-Rabiٔ (eds.), September 11: Religious Perspectives on the Causes and Consequences. Oxford: Oneworld Publications, 2002. x + 292 pp. $25.95 (paper). ISBN: 1851683089.